An Ultralight High-Directivity Ceramic Composite Lens Antenna for 220–330 GHz - Mikko Kokkonen (IEEE, 2021)
This work presents the characterization of Lithium molybdenum oxide (Li2MoO4, LMO) hollow glass microspheres (HGMS) ceramic composite from 0.1 to 1 THz and an associated bullet shaped lens used with WR3.4 for 220-330 GHz band. LMO-HGMS had permittivity of 1.18 and loss tangent of 0.003 at 300 GHz. The calculated reflectivity for the LMO-HGMS-air interface was 0.2 %. The fabricated bullet lens weighed 5 grams and was characterized using an experimental measurement system. The lens was measured to have a focus spot of diameter 1.5 mm. Simulated results showed the lens to operate with a WR3.4 waveguide having a gain of 27.5 dBi with a narrow beam width of 1-degree, 18 dB sidelobe level (SLL), 40% Fractional Beam Width (FBW), and −13 dB S11 over the broadband 220-330 GHz.